2016
DOI: 10.11646/phytotaxa.258.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Allopolyploid speciation in Siberian Dactylorhiza (Orchidaceae, Orchidoideae)

Abstract: Morphological and allozyme analyses of Siberian dactylorchids have revealed the presence of a new, previously undescribed allopolyploid that is described here as species new to science. The genetic constitution as revealed by allozyme analysis of this species confirms that its parents are the diploid Siberian D. fuchsii and D. incarnata, and it is 2n=80, representing the first such count from the Asiatic Russia. In most literature surveys of Siberia, the new species has been identified as D. baltica, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…Previous studies in diploid birch species have shown that HWE can generally be assumed (Rusanen, Vakkari, & Blom, 2003;Tsuda & Ide, 2005;Tsuda et al, 2015Tsuda et al, , 2009. Polyploids, especially allopolyploids, always display higher values of FIS, confirming nonrecombinant inheritance of parental genomes (Efimov, Philippov, & Krivenko, 2016;Lobato-de Magalhães et al, 2019).…”
mentioning
confidence: 73%
“…Previous studies in diploid birch species have shown that HWE can generally be assumed (Rusanen, Vakkari, & Blom, 2003;Tsuda & Ide, 2005;Tsuda et al, 2015Tsuda et al, , 2009. Polyploids, especially allopolyploids, always display higher values of FIS, confirming nonrecombinant inheritance of parental genomes (Efimov, Philippov, & Krivenko, 2016;Lobato-de Magalhães et al, 2019).…”
mentioning
confidence: 73%
“…However, we assume that the rank of variety is not appropriate for distinct allopolyploid taxa with different chromosome numbers. Allopolyploids with different evolutionary origins are usually classified at the species level, even if they share one or more parental species (e.g., Soltis & al., 2004; Kelly & al., 2013; Zou & al., 2015; Barker & al., 2016); in some cases, even the products of independent hybridization with an identical parental combination are being evaluated as separate species (mostly in apomictic genera, but also in allogamous species, e.g., Efimov & al., 2016). We also point out that C. hamulata and C. brutia subsp.…”
Section: Discussionmentioning
confidence: 99%
“…1). All plant names are given in accordance with the Flora Sibiriae (1987) as well as more recent taxonomic treatments of particular genera (Efimov et al 2016). Cypripedium macranthos Sw. is named according to Averyanov (2000).…”
Section: Methodsmentioning
confidence: 99%
“…2). According to Efimov et al (2016) we consider Dactylorhiza cruenta to D. incarnata and exclude D. maculata from the list of orchid species.…”
Section: Diversity Of Orchidaceae Species In the Study Areamentioning
confidence: 99%